PERANCANGAN REDESAIN LOGO MICOW PADANG - M.arief Zuhri; eliya pebriyeni (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Micow is one of the shops that provide pure milk in the city of Padang. This business was initiated by Ucok Andi Oktora since October 20, 2015 which is located at Jl. Gajah 08 Air Tawar Barat Padang City. This business already has a good image, but the fundamental problem of the Micow logo is that it does not yet have a strong identity as a brand, and has not yet applied the principles of a good and correct logo design.The purpose of designing the Micow logo redesign is to design a logo by applying good, correct design principles so that later it will present a unique, simple, easy to remember, flexible, fun, communicative, and consistent placement in all types of media that will be used as Micow's attraction itself to be increasingly recognizable.The analytical method used is a SWOT analysis. This design produces a manual book as the main media that contains the design of the logo redesign starting from the moodboard, concepts, grid systems, colors, typography. Supporting media used to support the main media include Business Cards, Envelopes, Letters, Stamps, Posters, X-banners, Packaging, Menu Lists, Stickers, T-shirts, Aprons.Keywords: Redesign, Logo, Micow